Prevalence of Avian Pathogenic Escherichia coli (APEC) Clone Harboring sfa Gene in Brazil. (30th April 2012) - Knöbl, Terezinha; Micke Moreno, Andrea; Paixão, Renata; Gomes, Tânia Aparecida Tardelli; Vieira, Mônica Aparecida Midolli; da Silva Leite, Domingos; Blanco, Jesus E.; Ferreira, Antônio José Piantino
Abstract : Escherichia coli sfa + strains isolated from poultry were serotyped and characterized by polymerase chain reaction (PCR) and amplified fragment length polymorphism (AFLP). Isolates collected from 12 Brazilian poultry farms mostly belonged to serogroup O6, followed by serogroups O2, O8, O21, O46, O78, O88, O106, O111, and O143. Virulence genes associated were: iuc 90%, fim 86% neuS 60%, hly 34%, tsh 28%, crl/csg 26%, iss 26%, pap 18%, and 14% cnf . Strains from the same farm presented more than one genotypic pattern belonging to different profiles in AFLP. AFLP showed a clonal relation between Escherichia coli sfa + serogroup O6. The virulence genes found in these strains reveal some similarity with extraintestinal E. coli (ExPEC), thus alerting for potential zoonotic risk.